Web-based Campus Virtual Tour Application using ORB Image Stitching - Triyanna Widiyaningtyas; Didik Dwi Prasetya; Aji P Wibawa (Proceeding of the Electrical Engineering Computer Science and Informatics, 2018)
Information disclosure in the digital age has demanded the public to obtain information easily and meaningful. In this paper, we propose the development of web-based campus virtual tour 360-degree information system application at the State University of Malang, Indonesia which aims to introduce the assets of the institution in an interesting view to public. This application receives a stitched or panoramic image generated through the ORB image stitching algorithm as an input and displays it in virtual tour manner. This paper realizes the image stitching algorithm to present the visualization of the 360-degree dynamic building and campus environment, so it looks real as if it were in the actual location. Virtual tour approach can produce a more immersive and attractive appearance than regular photos.